Cs2AgBiBr6 as a mixed anion perovskites for photovoltaic applications: A first-principle study - Wanniarachchi, C.P.; Eidsvåg, W.A.; Arunasalam, T.; Ravirajan, P.; Velauthapillai, D.; Vajeeston, P. (Elsevier, 2022)
Ab initio calculations were performed for cubic Fm-3 m (225) and tetragonal (I4/m) phases for Cs2AgBiBr6(CaB2). We used the Vienna Ab Initio Simulation Package (VASP) to calculate the ground state properties using two different exchange-correlation functionals, namely the Generalized gradient approximation method (GGA) and the screened hybrid functional as proposed by Heyd, Scuseria, and Ernzerhof (HSE06) method. Tetragonal Cs2AgBiBr6 phase was stabilized in the tetragonal phase. The bandgap (Eg) was calculated using HSE06 for the polymorphs optimized at the PBE level and it is found that they belong to the indirect bandgap. The calculated bandgap for cubic and tetragonal phases in HSE06 for Cs2AgBiBr6 were 1.97 eV, and 2.4 eV, respectively. The character of chemical bonding in CaB2 is discussed based on electronic structures, charge density, charge transfer, and bond overlap population analyses.
Keywords: Cs2AgBiBr6; Optoelectronic properties; Bandgap; Cubic; Tetragonal